2009
DOI: 10.1373/clinchem.2008.117952
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Prostate Tumor Cells Detected by Reverse Transcription-PCR in Men with Localized or Castration-Refractory Prostate Cancer: Concordance with CellSearch Assay and Association with Bone Metastases and with Survival

Abstract: Background: Reverse transcription-PCR (RT-PCR) assays have been used for analysis of circulating tumor cells (CTCs), but their clinical value has yet to be established. We assessed men with localized prostate cancer or castration-refractory prostate cancer (CRPC) for CTCs via real-time RT-PCR assays for KLK3 [kallikrein-related peptidase 3; i.e., prostate-specific antigen (PSA)] and KLK2 mRNAs. We also assessed the association of CTCs with disease characteristics and survival. Methods: KLK3, KLK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
108
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 27 publications
3
108
0
1
Order By: Relevance
“…3, 16 It is inapplicable to cancers of non-epithelial origin such as melanoma, brain cancers, and sarcomas as well as advanced metastatic disease where EpCAM expression is lost. 17,18 The immunomagnetic isolation procedure associated with CTC identification with the CellSearch system involves chemical and mechanical manipulation that creates challenges to culture these cells for downstream analysis.…”
mentioning
confidence: 99%
“…3, 16 It is inapplicable to cancers of non-epithelial origin such as melanoma, brain cancers, and sarcomas as well as advanced metastatic disease where EpCAM expression is lost. 17,18 The immunomagnetic isolation procedure associated with CTC identification with the CellSearch system involves chemical and mechanical manipulation that creates challenges to culture these cells for downstream analysis.…”
mentioning
confidence: 99%
“…In this case, prognostic markers which are expressed adequately in early stages should be considered as proper target for detection (Allan and Keeney, 2010). The most applicable markers in this regard include cytokeratin-19, cytokeratin-20 or CEA, and PSA or PSCA which are used to isolate CTCs in early stages of breast, colorectal, and prostate cancers, respectively (Stathopoulou et al, 2003;Allen-Mersh et al, 2007;Helo et al, 2009).…”
Section: Isolation and Purification Of Ctcs Using Microchip Technologymentioning
confidence: 99%
“…Hence, EpCAM is one expressed CTC‐associated biomarkers known, and CTC isolation techniques based on EpCAM antibodies are widely used 44, 45. The popular CellSearch system, which has been extensively used to capture and isolate CTCs from the blood of patients with cancers of the breast, prostate, and colon, employs a conjugation of EpCAM antibodies to ferrofluidic beads to enable the capture of CTCs through a magnetic field 46, 47, 48. In addition to EpCAM, several studies have reported that HER2 is overexpressed in CTCs of both metastatic and early breast cancer patients, and clinical data has shown that the change of HER2 status from low level expression to high level also occurred along with breast cancer recurrence and progression 49, 50.…”
Section: Biophysical and Biochemical Properties Of Ctcsmentioning
confidence: 99%